Research and analysis of energy consumption and energy saving in buildings based on photovoltaic photothermal integration - Yahan Cui; Xinyan Zhang (Scientific Reports, 2024)
Abstract In order to reduce the energy consumption of buildings, an air source heat pump assisted rooftop photovoltaic-thermal integration system is designed. The installation area of photovoltaic modules and collectors will not only affect the power side, but also affect the thermal side. Therefore, the basic architecture of the photovoltaic photothermal integration system is first established, and then the improved whale algorithm is used to optimize the photovoltaic photothermal integration system with the daily operating cost as the optimization goal. At the same time, the influence of the installation area of the photovoltaic photothermal module on the comprehensive performance of the system is analyzed, and the environmental and economic benefits of the photovoltaic photothermal system are analyzed. The results of the example show that the roof of the building has significant benefits in environmental protection and investment recovery period when the photovoltaic photothermal system with the optimal area ratio is installed on the roof of the building. The solar photovoltaic power generation system can reduce carbon dioxide emissions by 147.11 t within 25 years, and the solar collector system can save 170.5 thousand yuan in 1 year. It has achieved the purpose of saving energy, reducing carbon dioxide emissions and protecting the environment.